Influence of summer mungbean genotypes on grain yield and resource-use efficiency in Kandahar province of Afghanistan - Noorzai, Amin Ullah; Choudhary, Anil K. (Annals of Agricultural Research, 2017)
A field experiment was conducted at Experimental Farm of Afghanistan National Agricultural Sciences and Technology University (ANASTU), Kandahar, Afghanistan during April-June, 2015 to work-out the grain yield and resource-use efficiency of mungbean varieties viz. Mai-2008, Mash- 2008, NM-94, NM-98 and local cultivar ’Kunduzy’ under semi-arid conditions of Kandahar. The results indicated that Mash-2008 exhibited significantly highest grain yield while Kunduzy exhibited minimum seed yield. The Mash-2008 yielded 5.0, 34.9, 34.5 and 48% more yield as compared to Mai-2008, NM-98, NM-94 and ’Kunduzy’, respectively. The mungbean genotypes showed significant differences for total water-use efficiency (TWUE), irrigation water-use efficiency (IWUE) and economic water productivity (WPE). Mash-2008 exhibited highest TWUE (9.9 kg haâ€“1 mmâ€“1), IWUE (10.6 kg haâ€“1 mmâ€“1) and WPE (644 AFN haâ€“1 mmâ€“1) while ’Kunduzy’ recorded minimum TWUE (6.7 kg haâ€“1 mmâ€“1), IWUE (7.2 kg haâ€“1 mmâ€“1) and WPE (434 AFN haâ€“1 mmâ€“1). Overall, Mash-2008 outperformed in terms of grain yield, production-efficiency, monetary-efficiency, total water-use efficiency (TWUE), irrigation water-use efficiency (IWUE) and economic water productivity (WPE) over other mungbean cultivars in semi-arid conditions of Afghanistan.